2000
DOI: 10.1111/j.1748-5827.2000.tb03221.x
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging of syringomyelia in five dogs

Abstract: This report describes the use of magnetic resonance imaging (MRI) in five dogs to diagnose spontaneous syringomyelia. Four of the dogs had cervical syringomyelia associated with hydrocephalus, and one of these cases was analogous to the Dandy‐Walker syndrome in humans. The fifth dog had thoracic syringomyelia without hydrocephalus. It was possible to diagnose the condition antemortem in all of the dogs by MRI. It is suggested that MRI is a straightforward and effective tool for the antemortem diagnosis of syri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
14
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 15 publications
2
14
0
1
Order By: Relevance
“…Ventriculoperitoneal (VP) shunts are commonly used to divert the flow of cerebrospinal fluid (CSF) from the ventricles of the brain to the peritoneal cavity in human neurosurgery [11], and have proved to be an effective surgical treatment for hydrocephalus in dogs [15] and cats [23]. Several investigators [12,15,16,24] in the veterinary field have suggested magnetic resonance imaging (MRI) to be a useful technique for the antemortem diagnosis of several cranial and spinal disorders in animals. This article describes the clinical findings in, and management of, a cat with hydrocephalus and syringomyelia, together with temporal changes in MR images obtained before and after the insertion of a VP shunt.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Ventriculoperitoneal (VP) shunts are commonly used to divert the flow of cerebrospinal fluid (CSF) from the ventricles of the brain to the peritoneal cavity in human neurosurgery [11], and have proved to be an effective surgical treatment for hydrocephalus in dogs [15] and cats [23]. Several investigators [12,15,16,24] in the veterinary field have suggested magnetic resonance imaging (MRI) to be a useful technique for the antemortem diagnosis of several cranial and spinal disorders in animals. This article describes the clinical findings in, and management of, a cat with hydrocephalus and syringomyelia, together with temporal changes in MR images obtained before and after the insertion of a VP shunt.…”
mentioning
confidence: 99%
“…Syringomyelia has been defined as fluid-filled cavities in the substance of the spinal cord, with destruction of the nervous tissue [19]. Its cause is unknown, but it may be associated with or result from hydrocephalus [16,24]. Ventriculoperitoneal (VP) shunts are commonly used to divert the flow of cerebrospinal fluid (CSF) from the ventricles of the brain to the peritoneal cavity in human neurosurgery [11], and have proved to be an effective surgical treatment for hydrocephalus in dogs [15] and cats [23].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrocephalus and hydranencephaly have been found to occur concurrently with parvovirus infection (Tani et al 2001;Keating et al 2016). Taga et al (2000) reported acquired hydrocephalus and hydromyelia in a cat with FIP. Tani et al (2001) described a cat with hydrocephalus and syringomyelia, which tested positive for the parvovirus antigen but negative for FIP antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Syringomyelias include cavernous dilation of spinal cord parenchyma that does not communicate with the central canal and is not directly localized in the canal (Taga et al 2000). In T1-weighted sequences, ventricular widening and spinal cord cavities filled with cerebrospinal fluid were characterized by low signal intensity (Fig.…”
Section: Syringomyeliamentioning
confidence: 99%